SEASONAL VARIATIONS OF TISSUE CALCIUM AND PHOSPHORUS IN THE JUVENILES OF THE CATFISH, WALLAGO ATTU (BL. & SCHN.). - Jafri, A K; Khawaja, D K (Indian Journal of Fisheries, 2011)
Seasonal variations have been studied in calcium and phosphorus contents of muscle and liver of juveniles of the cat-fish, Walldgo attu (Bl. & Schn.)- The variations in the quantity of these minerals in the two tissues followed well-defln’3d cycles and these were identical in the juveniles of the two size-groups investigated. The rise and fall in the calcium and phosphorus values have been attributed mainly to the f’seding rhythm of these sexually immature fishes.